Hiệu quả công việc và vai trò trung gian của sự phát triển, tự chủ của nhân viên ngành trang trí nội thất tại thành phố Hồ Chí Minh - Huỳnh Thị Thu, Sương; Huỳnh Thị Đoan, Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The objective of this research is to explore and test the relationship of empowering leadership (EL) and its potential to promote thriving at work (TW) and job autonomy (JA), which, in turn, could improve employee performance (EP) from SMEs in the furniture industry in Ho Chi Minh city. Qualitative research results provide four background theories and scales for surveying 200 employees by using the stratification technique. The findings are tested through measurement models and structural equation modeling (PLS-SEM) using SmartPLS 4 to test the hypotheses and employ stratified techniques for sample selection. The findings indicated that there exists a positive influence of EL on EP; mediated partially by TW and JA. The results contribute to enhancing the role of TW and JA in studying the impact of leadership styles on employee performance in the research context in Vietnam. Research results suggest that managers should focus on the role of empowering leadership in creating a working environment of autonomy and thriving at work for employees to improve employee performance from SMEs in the furniture industry in Ho Chi Minh City.